2020
DOI: 10.1088/1757-899x/788/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of natural Bentonite from Aceh, Indonesia as filler of Poly-Caprolactone/Poly-Lactic Acid/Chitosan, (PCL/PLA/Chitosan) nanocomposites

Abstract: The formation of composite from polymer mixture PCL / PLA / Chitosan bentonite was carried out through the melt intercalation method using an extruder at 180 °C with a holding time of 20 minutes. Bentonite is obtained from Kab. North Aceh which has been modified with CTAB surfactant. The sample formulations used were single PCL and PCL polymers each given 3, 5 and 8 % chitosan fillers. A mixture of PCL / PLA (50: 50) was given 3, 5 and 8 % chitosan / bentonite fillers. The sample is a white plastic rod (bone) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…An example of such a mineral is bentonite-a naturally occurring clay mineral with very small particle sizes and a high degree of plasticity [22]. Studies showed that the introduction of an additive to the polymer matrix has a positive effect on the thermal and mechanical properties of the composite, such as hardness, tensile strength and elongation [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…An example of such a mineral is bentonite-a naturally occurring clay mineral with very small particle sizes and a high degree of plasticity [22]. Studies showed that the introduction of an additive to the polymer matrix has a positive effect on the thermal and mechanical properties of the composite, such as hardness, tensile strength and elongation [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%